Analysis of Compensation and Adaptive Leadership on Employee Performance Through Employee Engagement at PT PLN (Persero) ULP Lima Puluh - Yunita Panjaitan; Erwansyah; Hernawaty (CV. Doki Course and Training, 2026)
This study aims to analyze the effect of compensation and adaptive leadership on employee performance through employee engagement at PT PLN (Persero) ULP Limapuluh. This research adopts a quantitative approach using a survey method. The research sample consists of 78 employees selected using a saturated sampling technique. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that compensation and adaptive leadership have a positive and significant effect on employee engagement. Furthermore, compensation, adaptive leadership, and employee engagement also have a positive and significant effect on employee performance. Employee engagement is proven to mediate the relationship between compensation and adaptive leadership on employee performance. Therefore, improving a fair compensation system and implementing effective adaptive leadership can enhance employee engagement and ultimately improve employee performance at PT PLN (Persero) ULP Limapuluh.